(untitled) (Journal of Science and Technology, 2015)
The proteins in germinating millet were subjected to the Osborne-type protein fractionation, Though prolamins formed the major protein fraction In ungerminated millet. globulins became 10%e main protein fraction after 72 hours of germination, Analysis of amino acid composition of the protein fractions that millet proteins were deficient in the sulphur containing amino acids. However, upon controlled ger-Flirtation the bed no acids as well as the other essential arna acids were abundantly produced. Studies on t1 endopeptidase activity [EPA) Involved in the degradation of the millet proteins revealed that the ungerminated millet has an acidic endopeptidase, but a neutral end an alkaline endopeptidase were added in later stages of germination. The millet endopeptidase requires SH group and a divalent Ion for activity,